The Role of Family Communication in Dealing with Youth Impostor Syndrome during the Covid-19 Pandemic - As’adillah sudrajat, Abijar; Hasfi Mutiara Insani; Meiliani Maulidia Putri; Wilda Riva Fadhilah; Wina Nurhayati Praja (LPPM Stikosa - AWS, 2023)
Psychological problems are often found in the adolescent phase with an age range between 17-24 years and unmarried. These problems are related to impostor syndrome. It is very important for parents to know the phenomenon of impostor syndrome and how to communicate with children who experience this phenomenon. This study aims to determine the factors and impacts of impostor syndrome, as well as explain the role of family communication in dealing with impostor syndrome for adolescents during the Covid-19 pandemic. The research design uses a qualitative approach with a purposive sampling technique that selects samples based on criteria. Then, the data collection technique uses semi-structured interviews. The results of this study describe several factors that cause a teenager to experience impostor syndrome during the Covid-19 pandemic and its effects. In dealing with this phenomenon there are patterns of communication that can be done.